Forensic Psychologists Prisons, Power, and Vulnerability. - Warr, Jason (Emerald Publishing Limited, 2020)
Built on a large body of research relating specifically to forensic psychologists and prison life more generally, this book examines how this professional discipline has become central to life within the modern prison. Exploring a number of themes, it takes the reader behind the scenes of forensic psychological practice in Her Majesty's prisons.